Conduction effect in dielectric relaxation of Pb(Al ₀.₅V₀.₅)O₃ ceramic sample - Primus, Walter Charles; Shaari, Abdul Halim; Wan Yusoff, Wan Mohd. Daud; Talib, Zainal Abidin (Universiti Putra Malaysia Press, 2005)
The dielectric properties of Pb(Al ₀.₅V₀.₅)O₃ ceramic sample has been study using dielectric spectrometer from frequency range 1×10-2 to 1×106 Hz at five different temperatures. At 28 ⁰C and 50 ⁰C, the dielectric dispersion is dominated by quasi d.c at low frequency and dipolar at higher frequency. However, at 100 ⁰C and above, the relaxation peak has been mask by the conduction effect at low frequency. The activation energy obtained from the a.c conductivity for this sample in the range of 28 ⁰C to 200 ⁰C is 0.642 eV.